Hadith #462 - Al-Adab Al-Mufrad (Al-Adab Al-Mufrad)
‘A’isha, the wife of the Prophet, may Allah bless him and grant him peace, said, “A group of Jews came to the Messenger of Allah, may Allah bless him and grant him peace, and said, “Poison (‘sam’ instead of ‘salam’) be upon you.” ‘A’isha said, “I understood it and said, ‘And poison be upon you and the curse of Allah!’ The Messenger of Allah, may Allah bless him and grant him peace, ‘Easy, ‘A’isha! Allah loves compassion in everything.’ I said, ‘Didn’t you
Grade:

Hadith #463 - Al-Adab Al-Mufrad (Al-Adab Al-Mufrad)
Jarir ibn ‘Abdullah reported that the Messenger of Allah, may Allah bless him and grant him peace, said, “Whoever is denied compassion is denied good.”
Grade:

Hadith #464 - Al-Adab Al-Mufrad (Al-Adab Al-Mufrad)
Abu’d-Darda’ reported that the Prophet, may Allah bless him and grant him peace, said, “Whoever has been given his portion of compassion has been given his portion of good. Whoever is denied given his portion of compassion has been denied his portion of good. Good character will be the weightiest thing in the believer’s balance on the Day of Rising. Allah hates a coarse, foul-mouthed person.”
Grade:

Hadith #465 - Al-Adab Al-Mufrad (Al-Adab Al-Mufrad)
‘A’isha reported that the Prophet, may Allah bless him and grant him peace, said, “Forgive right-acting people their slips.”
Grade:

Hadith #466 - Al-Adab Al-Mufrad (Al-Adab Al-Mufrad)
Anas reported that the Prophet, may Allah bless him and grant him peace, said, “If there is roughness in anything it is bound to disgrace it. Allah is compassionate and loves compassion.”
Grade:

Hadith #467 - Al-Adab Al-Mufrad (Al-Adab Al-Mufrad)
Abu Sa’id al-Khudri said, “The Messenger of Allah, may Allah bless him and grant him peace, was more modest than a virgin in her tent. When he disliked something, we recognised that in his face.”
Grade:

Hadith #468 - Al-Adab Al-Mufrad (Al-Adab Al-Mufrad)
Ibn ‘Abbas reported that the Prophet, may Allah bless him and grant him peace, said, “Right guidance, good behaviour and aiming for what is just and correct is a seventieth part of prophethood.”
Grade:

Hadith #469 - Al-Adab Al-Mufrad (Al-Adab Al-Mufrad)
‘A’isha, may Allah be pleased with her, said, “I was on a camel which was somewhat intractable and the Prophet, may Allah bless him and grant him peace, remarked, ‘You must be compassionate. Whenever there is compassion in something, it adorns it, and when it is removed from something it disgraces it.”
Grade:

Hadith #470 - Al-Adab Al-Mufrad (Al-Adab Al-Mufrad)
Sa’id al-Maqburi reported from his father that the Messenger of Allah, may Allah bless him and grant him peace, said, “Beware of avarice. It destroyed those before you. They shed one another’s blood and broke off relations with their relatives. Injustice will appear as darkness on the Day of Rising.”
Grade:

Hadith #471 - Al-Adab Al-Mufrad (Al-Adab Al-Mufrad)
Kathir ibn ‘Ubayd said, “I visited ‘A’isha, the Umm al-Mu’minin, may Allah be pleased with her. She said, ‘Wait until I sew up my garment.’ So I waited and said, ‘Umm al-Mu’minin, when I go out, I will tell them that your enemy is miserliness.’ She said, ‘Look to your own business. There are no new clothes for anyone who does not wear shabby clothes.'”
Grade:

Hadith #472 - Al-Adab Al-Mufrad (Al-Adab Al-Mufrad)
‘Abdullah ibn Mughaffal reported that the Prophet, may Allah bless him and grant him peace, said, “Allah is compassionate and loves compassion. He gives for compassion what He goes not give for harshness.”
Grade:

Hadith #473 - Al-Adab Al-Mufrad (Al-Adab Al-Mufrad)
Anas ibn Malik reported that the Prophet, may Allah bless him and grant him peace, said, “Make things easy and do not make things difficult. Calm people and do not arouse their aversion.”
Grade:

Hadith #474 - Al-Adab Al-Mufrad (Al-Adab Al-Mufrad)
‘Abdullah ibn ‘Amr said, “A guest stayed among the tribe of Israel and there was a dog in the house. They said, ‘Dog, do not bark at our guest. The puppies were suckling from it. They mentioned it to one of their Prophets who said, ‘This is like a community which will come after you and whose fools will overcome its men of knowledge.”
Grade: